Knowledge and Attitude Relationship in Adolescent HIV AIDS Prevention: Hubungan Pengetahuan dan Sikap Pencegahan HIV AIDS pada Remaja - Utami, Arum Surya; Lestari, Susi; Astutik, Eftyaningrum Dwi Wahyu; Handayani, Endah Purwanti; Lestari, Tiyan Febriyani; Utami, Fetty Satu Ryan; Dinge, Fenny (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Adolescents represent a high-risk group for HIV/AIDS due to increased social interaction and limited access to accurate reproductive health information. Specific Background: In religious-based schools, discussions related to HIV/AIDS are often considered taboo, potentially restricting knowledge acquisition and shaping preventive attitudes. Knowledge Gap: Previous studies primarily focused on public or urban schools, with limited investigation of socio-cultural dynamics in Islamic-based educational settings. Aims: This study aims to determine the relationship between knowledge and attitudes toward HIV/AIDS prevention among adolescents at SMA IT Cendekia. Results: Using a cross-sectional design with 57 students, the findings revealed that 66.7% of respondents had good knowledge and 70.2% demonstrated positive attitudes. Statistical analysis showed a significant relationship between knowledge and attitudes (p = 0.008), indicating that higher knowledge levels are associated with more positive preventive attitudes. Novelty: This study situates the knowledge–attitude relationship within the context of an Islamic-based school, highlighting the role of socio-cultural and religious values in shaping adolescents’ perspectives. Implications: The findings emphasize the importance of providing accurate, comprehensive, and culturally sensitive HIV/AIDS education to support positive attitudes and strengthen prevention strategies among adolescents. Highlights • Majority of respondents demonstrated adequate understanding and favorable prevention perspectives• Statistical testing confirms association between cognitive level and preventive orientation• Religious-based school context reveals socio-cultural constraints in information access Keywords HIV/AIDS Prevention; Adolescent Knowledge; Preventive Attitudes; Cross Sectional Study; Religious Based School